Reference Gene Selection for Analyzing the Transcription Patterns of Two Fatty Acyl-CoA Reductase Genes From Paracoccus marginatus (Hemiptera: Pseudococcidae). Issue 5 (4th October 2021) - Liang, Xiao; Chen, Qing; Wu, Chunling; Liu, Ying; Han, Zhiling; Wu, Mufeng
Abstract: Paracoccus marginatus (Hemiptera: Pseudococcidae), known as the papaya mealybug, could cause considerable yield loss of several plants. To date, there is no molecular-based study of P. marginatus . Fatty acyl-CoA reductases (FARs) are key enzymes involved in wax synthesis. In the present study, we cloned and characterized coding sequences (CDS) of two FAR genes from P. marginatus . The results showed that PmFAR1 and PmFAR2 CDS were 1, 590 and 1, 497 bp in length, respectively, and sequence analysis indicated that these two genes both had the conservative motifs belonging to FAR_C superfamily. Furthermore, seven candidate reference genes were analyzed for their expression stability by using common algorithms including comparative ΔCq method, geNorm, NormFinder, BestKeeper, and RefFinder. Eventually, β -actin and GAPDH were the best reference genes in evaluating the expression of those two FAR genes. We found that PmFAR1 and PmFAR2 showed distinct expression patterns in different life stages. Moreover, the transcription of PmFAR1 and PmFAR2 in P. marginatus fed on resistant cassava cultivars was significantly lower compared with those fed on susceptible ones, indicating the potential function of FAR genes in cassava resistance to P. marginatus. The present study might help in better understanding the molecular mechanism of cassava resistance to mealybug.